(3GdTjN eMahX fMfGM (B:s (3ehGba aj GdOYhI h GdMQcI (B/s - (3Hf GdgGTej,ahRj ChUOjb s ((3GdLRGFQ (B:s (3OGQ GdGfJaGVI ,s, 1990)
(3gPG GdcJGH Gh HGdCNQi gPg GdSdSdI (B-(3fMhhYj MQcj(B-(3HLRFgG GdChd dGjbOe JGQjNG jYJeO Ydi GdhbGFY h GdCMOGK hEfeG jbOe JMdjd dTNUjI GdCSJGP eMahX fMfGL MJi Jchf TNUjJg fHQGSG hTYdI WQjb GdOYhI (B.s